2012
DOI: 10.4315/0362-028x.jfp-11-506
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a University Campus-Based Food Safety Media Campaign for Young Adults

Abstract: Food safety information campaigns are more likely to be most effective if the messages are tailored to the needs of a specific audience. Designing effective campaigns involves careful study of the target population and working with them using a community-based participatory research model. Thus, the development of the campaign materials for a university campus-based food safety media campaign for young adults followed intense efforts of working with the target audience to gather the baseline data needed to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 41 publications
2
36
1
3
Order By: Relevance
“…The researchers recognize respondents' self-reported food safety behaviors may not completely represent actual food safety behavior engagement (Abbot et al, 2012;Clayton et al, 2002;Mayer & Harrison, 2012) and serves as a limitation. Recognizing this, several interesting findings provided insight into consumers' self-reported food safety behaviors, preferred communication styles, and critical thinking styles, even though no substantial relationship between Florida residents' critical thinking style and food safety behaviors was found.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The researchers recognize respondents' self-reported food safety behaviors may not completely represent actual food safety behavior engagement (Abbot et al, 2012;Clayton et al, 2002;Mayer & Harrison, 2012) and serves as a limitation. Recognizing this, several interesting findings provided insight into consumers' self-reported food safety behaviors, preferred communication styles, and critical thinking styles, even though no substantial relationship between Florida residents' critical thinking style and food safety behaviors was found.…”
Section: Discussionmentioning
confidence: 99%
“…YouTube, Facebook, videos, and the internet were not only found as the preferred method of receiving food safety information, but researchers found these mediums contributed to an increase in food safety knowledge among participants (Mayer & Harrison, 2012). Abbot et al (2012) similarly found that print media, electronic media, and interactive events improved participants' food safety behaviors: self-ratings of food safety knowledge and skills, actual food safety knowledge, food safety self-efficacy, stage of change for safe food handling, and reported hand washing behaviors.…”
Section: Behavioral Changementioning
confidence: 99%
See 3 more Smart Citations